The Legal Basis for Sustainable Development as a Human Right - Karar Hadi Sahar Ghailan Al-Jubouri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Concern for sustainable development, but human rights are considered the most important issues that concern the world, and our dear country has witnessed many transformations in all fields and at different levels in the country, especially those that have a large majority in human rights, and we all know that Iraq has witnessed many challenges. After the events of 2003 until now, because the human being is the subject of the right and the rights, and the international community and the international and local organizations all insist on the activation, investigation and development of this right and the human rights. Where we have not seen any mechanism of operational and investigative mechanisms, I must focus on the effects of the activation and non-activation of this right, and from this point of view, pay attention to the statement of what is meant by sustainable development and developments, and do not forget the role of the United Nations in promoting the cycle of sustainable development, with the basic statement Legal and comprehensive human rights, stating the position of the Iraqi legislator for the year 2005.